The clue of the linoleum lederhosen - Anderson, M. T. (M.T. Anderson's thrilling tales, 2007)
Looking forward to a vacation, Katie, Lily, and Jasper attach their flying Gyroscopic Sky Suite to the Moose Tongue Lodge and Resort, where they mingle with other child heroes found in books and become embroiled in a mystery involving lederhosen-clothed quintuplets and a screaming ventriloquist.